Beyond Awareness: Governance, Structural Poverty and Nutritional Challenges among Musahars in Siraha, Nepal - Bhandari, Jhabindra; Basnet, Yojan; Chaudhary, Kabita; Magen-Fabregat, Carine (Nepal Journal of Multidisciplinary Research, 2025)
Background: Nutritional disparities among Nepal’s marginalized communities remain a critical public health concern, particularly in the context of federalization and shifting responsibilities for health governance. The Musahar community, among the most socio-economically excluded groups in Nepal, faces persistent challenges in accessing adequate nutrition and health services. While interventions have primarily emphasized awareness and behavior change, little attention has been paid to structural poverty and governance failures that limit the effectiveness of such approaches. This study highlights that nutrition interventions must integrate poverty alleviation, inclusive governance, and cultural sensitivity into program design. It provides ethnographic evidence that can help the Ministry of Health and Population revise Nepal’s Multi-Sector Nutrition Plan (MSNP) to ensure equity-focused, community-centered approaches Methods: This study draws on two weeks of ethnographic fieldwork in Sakhuwanankarkatti Rural Municipality, Siraha district. Data were collected through 24 in-depth interviews, 3 focus group discussions, participant observation, and participatory resource mapping with Musahar households, local officials, health workers, and community volunteers. Data were analyzed thematically using practice theory to explore how everyday practices of food, health, and care are shaped by structural constraints. Informed verbal consent was secured from all participants. Results: Findings show that despite increased awareness of nutrition, structural poverty, caste-based exclusion, and weak local governance prevent Musahar families from accessing diverse diets and consistent health services. Dietary taboos and traditional healing practices persist not as ignorance but as adaptive responses to poverty and exclusion. Federalization has not translated into improved service delivery: local governments face limited budgets, weak accountability, and dependence on NGOs for nutrition interventions. Trust deficits between communities and health institutions further undermine the effectiveness of nutrition programs. Conclusion: Awareness-focused interventions alone cannot address the nutritional challenges faced by the Musahar community. Structural poverty, exclusion, and weak local governance under federalism reproduce health inequities despite policy commitments to inclusivity. Effective interventions must go beyond awareness-raising to address structural barriers, strengthen accountability in local governance, and enhance social protection for marginalized groups.